Chlorophyll-ɑ Concentration of Periphyton attached in the plastic substrate placed in the Sail River, Pekanbaru City, Riau Province - Putra, Aldo Pratama; Dahril, Tengku; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTPeriphyton is one of microorganisms that serve as primary producer in the aquatic environment. Research aims to determine the chlorophyll-ɑ concentration of periphyton attached in plastic substrate has been carried out in April-May 2018 in the Sail River. There were three sampling stations, namely S1 (in the upstream), S2 (in the middle) and S3 (in the downstream). Samplings were conducted once/week for a 3 weeks period. The periphyton samples were brushed from the plastic substrates (8 x 6) cm2. Water quality parameters measured were water current, temperature, transparency, pH, dissolved oxygen, free carbon dioxide, nitrate, and phosphate. Results shown that chlorophyll-ɑ concentration of peripyhton in the plastic substrate in the S1 was 11.29 μg/cm², in S2 was 14.52 μg/cm²and in S3 there was 26.21 μg/cm². The water quality parameters were as follows: water current 0.07-0.69 m/s, transparency 6.03-7.67 cm, temperature 29-30 0C, dissolved oxygen 4.8-5.7 mg/L, free carbon dioxide 13.6-14.6 mg/L, nitrate 0.29-0.38 mg/L, phosphate 0.34-0.54 mg/L. The chlorophyll-ɑ concentration indicate that the trophic status of the Sail River was eutrophic. The water quality is good and it may be able to support the life of aquatic organisms. Keywords: Lotic, sessile organism, trophic state, water quality